PENGARUH FUNGI MIKORIZA ARBUSKULA DAN NUTRISI ORGANIK TERHADAP PERTUMBUHAN TANAMAN CABAI MERAH BESAR (Capsicum annuum L.) - Arma, Makmur Jaya; Risnawati, Risnawati; Gusnawaty, HS (Jurnal Agroteknos, 2013)
The research to study the effects of arbuscular mycorrhiza fungi (AMF) and organic nutrients to enhance the growth of chili has been conducted in Experimental Field, Faculty of Animal Husbandry and laboratory of Agrotechnology, Halu Oleo University, from June to November 2012.  The research was based on the split-plot design with a randomized  block design pattern (RAK) of two factors: Organic Nutrition as the main plot and AMF as subplot. Organic nutrients as the main plot consisted of three levels, namely: without organic nutrition (S0), 1 mL L-1  of water (S1) and 2 mL L -1  of water (S2);   and AMF dose as subplot consisted of three levels, namely: without AMF (M0), 5 g plant-1  (M1) and 10 g plant-1  (M2). therefore, there were 9 combinations of treatments and each treatment combination was repeated  three  times  to  obtain  27  experimental  units.  Each  variable  was  analyzed  by analysis of variance, then followed by Duncan's Multiple Range Test (UJBD) at 95% confidence level. The results of research indicated that the best interaction of   AMF   and organic  nutrient  treatment was 10 g AMF plant-1 (M2) and 2 mL L-1 (S2) of organic nutrients. This treatment combination can improve growth on variables: leaf area, leaf area index and yield index of the chili plants.  The best treatment for AMF independently was at 10 g plant-1 (M2) because it can promoted growth of plant height of the chili plants. The best treatment for organic matter independently was at 2 mL L-1(S2), because it can promoted growth of plant height of the chili plants. Keywords: FMA, organic nutrition, growth, chili